How Does Endothelial Permeability Affect the Development of Juvenile Idiopathic Arthritis? Vascular Endothelial Cadherin as a Promising New Tool Helpful in the Diagnostic Process. (21st October 2020) - Orczyk, Krzysztof; Smolewska, Elzbieta
Abstract : Introduction . Vascular endothelial cadherin (VE-cadherin) is a calcium-dependent protein essential for stabilization of the adherens junctions of the endothelial cells. Through vasculogenic mimicry, VE-cadherin may influence angiogenesis in synovial fibroblast-like cells. The soluble extracellular domain of VE-cadherin may be considered an indicator of endothelial dysfunction. Its potential as a diagnostic biomarker in rheumatic diseases, including juvenile idiopathic arthritis (JIA), needs to be investigated. Materials and Methods . The study group included 80 patients diagnosed with JIA. In 53 individuals, blood samples were obtained twice with an average interval of 102.4 ± 4.6 days. Results from the study group were compared to 29 age- and sex-matched healthy children. Results . Serum levels of VE-cadherin were significantly higher in JIA patients than in healthy controls. In such comparison, VE-cadherin had 87.5% sensitivity and 69.0% specificity for the cutoff level 4.36 ng/ml (Youden index 0.56, area under the curve 0.724). VE-cadherin concentrations negatively correlated with the disease activity score. However, such finding may be a false result because of the downregulation of VE-cadherin induced by glucocorticosteroids. Conclusions . VE-cadherin may become a promising diagnostic biomarker of early stages of JIA. Its predictive significance may be decreased by utilization of glucocorticosteroids. A multicentre study including patients with other arthritides is recommended for further evaluation of this protein.